Global Health Collaboration: Challenges and Lessons - Winchester, Margaret S.; Knapp, Caprice A.; BeLue, Rhonda (SpringerBriefs in Public Health, 2018)
global health collaboration; global health education; urban health; multiple morbidities; global health research; international university partnerships; sustainability; public health; multi-morbidity; transcultural; interdisciplinary and multi-institutional model; capacity building in global health; urbanization and health; intersection of infectious diseases and NCDs; non-communicable diseases (NCDs); health equity; health policy; health administration; healthcare disparities